THE USE OF MORPHEMES: AN ALTERNATIVE WAY TO INCREASE THE MASTERY OF STUDENTS’ VOCABULARY - Novita, Dian (Educate, 2014)
Dian Novita Universitas Muhammadiyah Sidoarjo dheenov@yahoo.com Abstract Using morphemes in English teaching and learning process is essential to increase the mastery of students‟ vocabulary. In the case, morphemes are the powerful aspects to build words. The article is intended to propose the importance of morphemes as one of linguistic approaches to help the learners figure out the meaning of unknown words by combining morpheme clues and context clues. In addition, it is expected that English teachers can apply the method in their teaching and learning process. Here, the method is divided into three phases: the instructional phase, the practice phase, and reviews and assessments. Keywords: morphemes, English teaching and learning process, vocabulary Abstrak Menggunakan morfem dalam proses belajar mengajar bahasa Inggris sangat penting untuk meningkatkan penguasaan kosakata peserta didik. Dalam kasus ini, morfem adalah aspek kuat untuk membangun kata-kata. Artikel ini dimaksudkan untuk menunjukkan pentingnya morfem sebagai salah satu pendekatan linguistik untuk membantu peserta didik mengetahui arti dari kata-kata yang tidak diketahui dengan cara menggabungkan petunjuk-petunjuk morfemik dengan petunjuk-petunjuk kontekstual. Selain itu, para pengajar bahasa Inggris diharapkan dapat menerapkan metode tersebut dalam proses belajar mengajar mereka. Di sini, metode ini dibagi menjadi tiga tahap: tahap pembelajaran, tahap praktek, dan tahap ulasan dan penilaian. Kata kunci: morfem, proses belajar mengajar bahasa Inggris, kosakata